Control your dreams : how lucid dreaming can help you uncover your hidden desires, confront your hidden fears, and explore the frontiers of human consciousness - Gackenbach, Jayne; Bosveld, Jane (My University, 1989)
Outlines a dream technique that enables sleepers to be both actors and director of their dreams by remaining in a state of semi-consciousness.
Keywords: dreams; success